Antecedents Of Employee Engagement In Gen Y - Mega Asri Zona; Fauziah aini (Universitas Negeri Padang, 2021)
This study aims to analyze: (1) the effect of distributive justice on employee engagement on millennial employees in North Sumatra. (2) the influence of procedural justice on employee engagement on millennial employees in North Sumatra (3) the influence of interactional fairness on employee engagement on millennial employees in North Sumatra (4) the influence of transformational leadership on employee engagement on millennial employees in North Sumatra. This research is causal research. The population in this study was employees of millennials in North Sumatra. With non probability sampling technique that is purposive sampling. The sample in this study was 300 people. With analysis techniques through SPSS 20.0. The results of this study found that: (1) distributive justice has a positive and significant effect on employee engagement in millennials in North Sumatra, (2) procedural justice has a significant positive effect on employee engagement in millennials in North Sumatra (3) interactional justice has a positive and significant effect on employee engagement in millennials in North Sumatra (4) transformational leadership has a positive and significant effect on employee engagement to millennials in North Sumatra.